ИЗУЧЕНИЕ ИЗБЫТОЧНОЙ МАССЫ ТЕЛА И ОЖИРЕНИЯ СРЕДИ ШКОЛЬНИКОВ (Multidisciplinary Journal of Science and Technology, 2026)
This article examines current global trends in the prevalence of obesity among school-age children (5–19 years old), analyzing risk factors, health consequences, and key prevention strategies. The analysis draws on data from international organizations and epidemiological studies demonstrating a significant increase in the number of overweight and obese children in recent decades. It notes that childhood obesity is becoming not only a problem in developed countries but also a clear trend in many regions of the world, requiring comprehensive measures in health and nutrition policy.